The Perceived Performance Of Construction Firms In The United Arab Emirates In The Context Of Total Quality Management Environment - Shakir, Firas Jalal (2011)
This study was carried out to compare and contrast the performance of construction firms that implement the TQM philosophy and the ones that do not via statistically measuring three major indicators of performance (i.e. employee satisfaction, operational effectiveness and customer satisfaction). Furthermore, this study aimed to highlight the benefits of TQM implementation in the construction industry. The theoretical framework for the study was drawn from the European Foundation Quality Model (EFQM, 2010). A correlational research employed a purely quantitative approach to gather information on employees from some construction firms in Dubai and their performance. 321 employees were randomly selected from some construction firms in Dubai.